On the Origin of Biomolecular Networks - Janwa, Heeralal; Massey, Steven E.; Velev, Julian; Mishra, Bud (Frontiers in Genetics, 2019)
Bio-molecular networks have already found great utility in characterizing complex biological systems arising from pairwise interactions amongst bio-molecules. Here, we explore the important and hitherto neglected role of information asymmetry in the genesis and evolution of such pairwise bio-molecular interactions. Information asymmetry between sender and receiver genes is identified as a key feature distinguishing early biochemical reactions from abiotic chemistry, and a driver of network topology as bio-molecular systems become more complex. In this context, we review how graph theoretical approaches can be applied not only for a better understanding of various proximate (mechanistic) relations, but also, ultimate (evolutionary) structures encoded in such networks from among all types of variations they induce. Among many possible variations, we emphasize particularly the essential role of gene duplication in terms of signaling game theory, whereby sender and receiver gene players accrue benefit from gene duplication, leading to a preferential attachment mode of network growth. The study of the resulting dynamics suggests many mathematical/computational problems, the majority of which are intractable yet yield to efficient approximation algorithms, when studied through an algebraic graph theoretic lens. We relegate for future work the role of other possible generalizations, additionally involving horizontal gene transfer, sexual recombination, endo-symbiosis, etc., which enrich the underlying graph theory even further.